Reproductive Behavior of Female University Students in Relation to Endocrine Regulators Concentration in Blood Plasma during Ovarian Cycle - Matejovičová, Barbora; Vondráková, Mária; Boledovičová, Mária; Pôbišová, Alexandra; Žatko, Tomáš; Sirotkin, Alexander (OMICS International Group, 2016)
The aim of our work based on answers of Slovak women - university students that are representing an important target group, was to analyse their reproductive behaviour and opinions, because the behaviour and opinions concerning reproduction could differ significantly depending also on education. Our goal was to analyze associations among reproductive behaviour of university student girls, their opinions and concentrations of endocrine regulators (insulin-like growth factors IGF-1, estradiol, testosterone and progesterone) in the blood serum and record their changes during the ovarian cycle. The group under study encompassed 301 female university students aged 19 ±1.371 years. Analysis of reproductive behaviour characteristics were based on a questionnaire method. Concentrations of the IGF-1, testosterone, estradiol and progesterone in blood plasma according to ovarian cycle phase had been set by biochemical methods and then linked with reproductive behaviour. Average value of sexual debut for girls was 17.21 ± 1.31 years. Most of them get over their first sexual intercourse in the age of 19 and almost half of them had one sexual partner. Differences in hormone concentrations were proved according to ovarian cycle phase for estradiol and progesterone, but no differences were found for testosterone; physiological role of IGF-1 during ovarian cycle did not alternate. IGF-1 influenced regulation of female students´ opinion of optimum age for sexual life beginning, their attitude to gender identity and marriage planning. Satisfaction with sexual identity was associated with higher blood estradiol level (but not with testosterone and progesterone levels). The outputs given in this work can help identifying insufficiently known relations between less known endocrine regulators (IGF-1) and reproductive behaviour of young women.
Keywords: Insulin-like growth factor IGF-1; Estradiol; Testosterone; Progesterone; Reproductive behavior; Female university students